2011
DOI: 10.1007/s00259-011-1877-y
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear myocardial perfusion imaging with a novel cadmium-zinc-telluride detector SPECT/CT device: first validation versus invasive coronary angiography

Abstract: In this first report on CZT SPECT/CT MPI comparison versus angiography we confirm a high accuracy for detection of angiographically documented CAD. Methods The study population included 66 patients (79% men; mean age 63±11 years) who underwent one day 99m Tc-tetrofosmin pharmacologic stress/rest examination and angiography within 3 month. Sensitivity, specificity, positive (PPV) and negative predictive value (NPV) as well as accuracy of the CT x-ray based attenuation corrected CZT MPI for detection of CAD (≥ 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 23 publications
(35 reference statements)
0
44
1
3
Order By: Relevance
“…After 392 6 47 MBq of 99m Tc-tetrofosmin had been administered, stress MPI images were acquired approximately 60 min later (during 5 min) on the CZT camera. This acquisition was followed by rest MPI using the identical protocol several minutes after administration of a 3 times higher dose of 99m Tctetrofosmin (1,143 6 133 MBq), as previously validated (9,10). MPI scans were acquired using a multipinhole collimator and 19 stationary detectors simultaneously imaging 19 different views of the heart as previously reported (6).…”
Section: Image Acquisitionmentioning
confidence: 99%
“…After 392 6 47 MBq of 99m Tc-tetrofosmin had been administered, stress MPI images were acquired approximately 60 min later (during 5 min) on the CZT camera. This acquisition was followed by rest MPI using the identical protocol several minutes after administration of a 3 times higher dose of 99m Tctetrofosmin (1,143 6 133 MBq), as previously validated (9,10). MPI scans were acquired using a multipinhole collimator and 19 stationary detectors simultaneously imaging 19 different views of the heart as previously reported (6).…”
Section: Image Acquisitionmentioning
confidence: 99%
“…In this study it was concluded that abnormal perfusion revealed the hemodynamic significance of anatomic lesions on angiography and was able to show coronary atherosclerosis before clinical symptoms indication and played a major role in the decision to angiography; also a normal perfusion scan, which has rejected a normal ischemia, cannot rule out ischemic coronary artery disease (33). Fiechter et al (2011) obtained a sensitivity of 87% and specificity of 67% for myocardial perfusion imaging (34). In all these studies, the sensitivity and specificity of myocardial scintigraphy was estimated at a high level, representing the diagnostic value of this method.…”
Section: Discussionmentioning
confidence: 99%
“…The 1-d 99m Tc-tetrofosmin adenosine stress (0.14 mg/kg/min over 6 min)/rest electrocardiogram-gated imaging protocol was previously described in detail (9)(10)(11). In brief, 60 min after the injection of 300-350 MBq of 99m Tc-tetrofosmin, images were acquired (over 5 min) with a cadmium-zinc-telluride camera, a tracer dose 3 times higher than the stress dose was injected, and image acquisition was initiated within a few minutes.…”
Section: Image Acquisition and Analysismentioning
confidence: 99%